Gender and the development of Didactic Writing, 1775-1816 - Rubio, Jennie J. (The University of Edinburgh, 1998)
Although there have been numerous studies of the ideas associated with the eighteenth century Enlightenment, few studies have looked at these ideas in relation to women writers.

This thesis examines in particular a set of ideas referred to as "moral sensibility" in terms of the development of women's writing in the late eighteenth century. Thinkers such as Francis Hutcheson and Hugh Blair suggest, among other things, that human happiness lies in pursuing certain kinds of "pleasure" while controlling the appetite for others. The implication that many writers took from this thinking is that promoting one kind of pleasure over another will lead to greater social harmony. This thesis discusses how a variety of women writers exploit these ideas and use them to evolve a tradition of didactic writing. This tradition of writing claims to be promoting one kind of pleasure while discouraging another. For women writers, "pleasure" which is depicted as being morally healthy is associated with the values of domestic femininity: modesty, cleanliness and propriety. I will discuss how women writers often oppose this to what is described as "pleasure" which is depicted as being morally dangerous.

The texts I discuss in this thesis have in common their setting in the Highlands of Scotland. This is because another popular topic found in late eighteenth century writing is "primitivism," a theory about the evolution of society from the primitive towards the civilised. In many cases, it is argued that this evolution sees the loss of a natural "simplicity" of moral sensibility, an ability to appreciate the right kinds of pleasure. Primitivism often takes the Highlands, seen to be less developed than the rest of Britain, as an example of the evolution of society and of human sentiment (what Thomas Blackwell calls a "moral or philosophical History of the World"). Many women writers describe their experience of the Highlands in terms of its "simplicity," and the lesson it can teach its readers. This thesis examines the development of women's writing which takes the Highlands as its subject and has the stated aim of "improving" its reader.